Prediksi Arus Kas Masa Depan Melalui Persistensi Laba Dan Komponen Akrual - Muhamad Safiq; Andi Ina Yustina; Karinna Firdiastella (FIRM Journal of Management Studies, 2018)
This study aims to develop the beliefs and components of accruals related to the components thatexist, at the same time in the Indonesia Stock Exchange (BEI). The data used in this research is paneldata, from 2011 until 2015 with the number of companies as much as 58 manufacturing companies,totality of data in this industry as much as 290 data. Hypothesis testing in this research using OLSapproach with analysis tool. Eviews 9. As for, the results of this study indicate that the persistence ofpositive spiders on the future, but the relevant accrual components that arise during this time. .Meanwhile, simultaneous does not reflect future cash futures. An alternative test resulted in a positiverelationship to future cash flows, where responsibility would not happen to the future. Here,diseminahkan, donated by positive to the future.